Chromomycosis Treatment With Combination Of Itraconazole And Terbinafine - Amalia Rositawati; Sunarso Suyoso (Faculty of Medicine, Universitas Airlangga, 2017)
Introduction: Chromomycosis is a localized chronic mycosis of skin and subcutaneous tissue caused by pigmented fungi. It is most common in tropical regions. Lesion usually presented with trauma history, and characterized by nodular verrucous that grow slowly on the lower extremities. The disease is difficult to treat. Case Report: A 33-year-old male garderner came with the main complaint multiple bumps accompanied with itchy and pain sensation on left leg that has became wider since 15 years before. There was a history of a thorn trauma in his left lower extrimity and he used to contact with soil and plants. The patient was diagnosed as chromomycosis based on history, clinical features, and confirmed with potassium hydroxide 10% that showed muriform cell, and fungal culture revealed the species Fonsacaea pedrosoi. The patient has not improved significantly treated with ketoconazole 200 mg 2 times daily for 9 months. The treatment was replaced into itrakonazole 100 mg 2 x 2 tablets combined with terbinafine 250 mg 2 x 1 tablets for 7 months and it gave a good result. Discussion: Predisposing factors in this case were a history of thorn trauma and contact with soil and plants continously. The lesions improved after 7 months treated with itraconazole and terbinafine. Chromomycosis is very difficult to treat and until now the gold standard treatment is not available yet. Combination therapy, itraconazole and terbinafine, could be considered for the therapy of chromomycosis with good result. Combination therapy can be continued until 2-4 weeks after no palpable nodules anymore.